ChemInform Abstract: Tetrafluorobromates for Urban Mining of Noble Metals: A Case Study on Iridium Metal. Issue 52 (24th December 2013) - Ivlev, Sergey; Woidy, Patrick; Kraus, Florian; Gerin, Ivan; Ostvald, Roman
Abstract The products of the solid state reaction of Ir metal with MBrF4 (M: K, Rb, Cs) and Ba(BrF4)2 in nickel ampoules at 400 °C for 150 min are characterized by powder XRD and simultaneous thermogravimetric and differential thermal analyses.